(untitled) (Global Journal of Management and Business Research, 2014)
Traditionally, the role of banks in any economy consists of financial intermediation, provision of an efficient payment system and serving as a conduct for the implementation of monetary policies. It is has been postulated that if these functions are efficient, the economy would be able to mobilize meaningful level off savings and channel such frauds to deficit unit, which will increase the gross domestic product (GDP) and create employment in long-run. This objective of this study is to investigate the implications of regulatory inconsistencies on the Nigerian banking industry. Regulation generally points to some kind of intervention in any business which ranges from explicit legal control to informal peer group control by government or some other such authoritative bodies. The methodology used in carrying out this work is descriptive desk research. The findings shows that regulatory in consistencies of Central Bank of Nigeria (CBN), Nigeria Deposit Insurance NDIC, Financial regulatory coordinating committee (FRSCC) have not guaranteed effective & efficient banking practices in Nigeria. Also each administrative regime propound new banking regulation that is abounded by the next regime thereby contributing to bank distress & failure. We recommend that regulatory agencies should be more proactive and be consistent regulatory policies; critical analysis should be carried out before implementation and the use of professionals and academia is necessary for the achievement of regulatory & supervisory policies in Nigerian banking system.